Controlled Drainage as a Targeted Mitigation Measure for Nitrogen and Phosphorus. Issue 3 (1st May 2019) - Carstensen, Mette V.; Børgesen, Christen D.; Ovesen, Niels B.; Poulsen, Jane R.; Hvid, Søren K.; Kronvang, Brian
Abstract : Drainage systems provide a more or less direct conduit for excess water and nutrients from fields to surface water. High nutrient loads to streams and lakes are known to adversely affect water quality and may potentially cause algae blooms. Therefore, in‐field as well as edge‐of‐field mitigation measures that can assist in reducing the loss of nutrients are needed. The aim of this study was to investigate the effectiveness and possibility of using controlled drainage during the drainage season to reduce nutrient losses while growing a winter crop in a temperate climate. The 3‐yr‐long (2012–2015) study was conducted on four experimental field plots on loamy soil. The impacts of controlled drainage on groundwater levels, drain flow, and water quality at regulation levels of 50 and 70 cm above the conventional drain pipe level were determined by using a before‐after control‐impact study design. A regulation level of 70 cm was required to significantly elevate groundwater levels and reduce the drain outflow and N and P loss, which decreased by 37 to 54%, 38 to 51%, and 43 to 46%, respectively, relative to conventional drainage levels. Denitrification in the root zone, as measured with stable isotopes, was not markedly enhanced at the plots with controlled drainage, except on a few occasions. Resetting the groundwater level to conventional levels in early spring only had a marginal influence on water and nutrient losses. Thus, potential water quality tradeoffs (e.g., increased N loss to groundwater) need to be more thoroughly investigated before implementing controlled drainage as a mitigation measure in Denmark. Core Ideas: Controlled drainage reduced the N and P loss from drainage systems. The reduction of N and P loss was mainly due to reduced drain flow. Denitrification was evident both at field plots with and without controlled drainage. Controlled drainage is not officially accepted as a mitigation measure in Denmark.